Proverbs and Sayings in the Novel “Vukadin” by Stevan Sremac – Frequency and Meaning - Sovrlić, Aleksandra N. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The research in this paper deals with a topic that hasn’t been much researched in literary theory. The topic is the presence of proverbs and sayings and their importance in the literary work of Stevan Sremac. The notebooks Stevan Sremac used, as well as his passion for collecting rare words, names, toponyms, and proverbs, are well known in literary history. Therefore, an important aspect for the analysis of his work is the way he incorporated the impalpable linguistic and national treasures from the places he visited (Senta, Belgrade, Niš) into his literary work. By studying proverbs and sayings in his novel Vukadin, we wanted to point out the fact that these two short folk prose forms, proverbs and sayings, unexpectedly and greatly influenced the novel in all of its essential elements: in portraying and characterization of the characters, construction of humor, in the depiction of the mentality of the people in an area and the national mentality in general, in the describing the situations, comments on the individual events, and above all, in pointing out the writer’s thoughts and ideas. Subsequently, in a wider context, this testifies not only to the richness of the Serbian folk language and the fact that Serbian people like to express themselves through these forms, but also to the linguistic and narrative mastery and knowledge of Stevan Sremac, who skillfully and unobtrusively wove more than one hundred and thirteen proverbs and sayings into his literary fabric.